أثراستخدام الحاسوب في تعلم طلبة معھد الدراسات الموسیقیة مادة النظریات الموسیقیة - أسيل سعد الدين شمس الدين (مجلة الفتح للبحوث التربوية والنفسية, 2024)
The effect of using computers in the learning of students at the Institute of Music Studies in the subject of music theory.